DATOS BIOLÓGICOS Y D ESCRIPCIÓ N DE ESTADOS INMADUROS DE EXOCHONOTUS EUGENIAE (C O LEO PTERA : CLERID A E: EN O PLIIN A E) - Solervicens A., Jaime (Acta Entomológica Chilena, 2022)
The association of Exochonotus eugeniae to plants of Euphorbia lactiflua affected by xylophagous insects and their restricted geographic distribution in the Pan de Azúcar National Park (26°08’S), III Región, Chile, are recognized. A probable competitive displacement is suggested between Exochonotus eugeniae and Inhumeroclerus thomsoni in the Coastal zone of the desert inhabiled by Euphorbia lactiflua. The mature larvae and the pupa of the species are described.